2021
DOI: 10.1155/2021/5559616
|View full text |Cite|
|
Sign up to set email alerts
|

Development of High Accuracy Classifier for the Speaker Recognition System

Abstract: Speech signal is enriched with plenty of features used for biometrical recognition and other applications like gender and emotional recognition. Channel conditions manifested by background noise and reverberation are the main challenges causing feature shifts in the test and training data. In this paper, a hybrid speaker identification model for consistent speech features and high recognition accuracy is made. Features using Mel frequency spectrum coefficients (MFCC) have been improved by incorporating a pitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The vocal aperture not only influences the geographic roots, but also the voice pitch, the flow and structural characteristics [9]. The speaker recognition systems are also highly used to track a speaker's presence.…”
Section: Physiology Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The vocal aperture not only influences the geographic roots, but also the voice pitch, the flow and structural characteristics [9]. The speaker recognition systems are also highly used to track a speaker's presence.…”
Section: Physiology Representationmentioning
confidence: 99%
“…These short-term sensory functions were formulated for the identification of the signal community and the emotion of certain speaker functions. Work was done with entropy and probabilistic methods for recognizing wrath [9]. In order to produce function score and calculate relative weights the author has processed the acoustic and linguistic features.…”
Section: ░ 2 System Modelmentioning
confidence: 99%
“…A person's claimed identity may be verified or authenticated using recognition in either identification or identification mode (the system determines the best match from the full enrolled population) are examples of this [6], [7]. Since the 1970s, techniques of speaker recognition have been deemed "classic" in the field of biometrics [8], [9]. The acoustic characteristics of each speaker are extracted by speaker identification systems from the spoken stream [10]- 1398 [12].…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic characteristics of each speaker are extracted by speaker identification systems from the spoken stream [10]- 1398 [12]. The following characteristics are reflected in: i) Anatomy: the geometrical and size forms of the voice lips, velum, lungs, teeth, tongue and lips cords [13]; ii) learned behavioral patterns: the manner in which one speaks [14]; Learning: the manner in which one speaks [9].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%